Categories and Context of Taboo Words in Denpasar (How Words Are Classified as Taboo) - I Made Astu Mahayana,; Ni Made Suwendri,; Made Sani Damayanthi Muliawan,; I Gusti Ayu Agung Dian Susanthi, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Taboo expressions are part of a language that is produced by culture. Every language in an area certainly has taboo expressions, including Denpasar City. Denpasar City is an industrial center that attracts everyone from various regions to settle and survive. With the phenomenon of immigrants with various backgrounds, there is an intensity of multi-language. On the other hand, technological advances slowly change language norms, especially the use of taboo words. This study aims to examine taboo words and analyze the context of an utterance that becomes taboo. This study uses a qualitative approach. Data was obtained through field studies and literature. This study also employs the theory of ethnographic and anthropological linguistics approaches. The results show that taboo expressions in Denpasar are divided into four categories: language level of taboo, naming taboo, context-specific taboo words, and general taboo words. In addition to the context, an utterance that becomes taboo is not only influenced by the word but is the result of a combination of performance and participants in the process of its expression. Thus, an utterance becomes taboo or inseparable from several elements, namely what utterance is used, how the utterance is used, where the utterance is used, who is involved, and what is meant by the said utterance.